Complication of using an orthodontic retainer: Komplikasi penggunaan retainer ortodontik - Khadijah; Eka Erwansyah (Makassar Dental Journal, 2020)
Background: The retention phase is a phase of orthodontic treatment that maintains the teeth in the corrected position after orthodontic appliance is removed. Retention appliances prevent the tendency of the teeth to return to the position before the orthodontic treatment. But apparently, in its use, the orthodontic retainer not only provides benefits but also can lead to any complications. Conclusion: There are some complications that can happened, such as retainer failure, periodontal impact especially gingival recession and bleeding during probing, demineralization on the enamel surface, and relapse or unexpected complication like rotation of the canines and different torque on the adjacent incisivus.